Social prescribing for frequent attenders in primary care: An economic analysis - Lynch, Mary; Jones, Ceri R. (Frontiers in Public Health, 2022)
Background: Social prescribing (SP) is a mechanism to link patients with community groups and third sector organisations. It offers a complimentary approach to the traditional medical models to address psychosocial needs of patients more effectively and in turn aims to reduce demand on the NHS. The aim of this study was to explore the economic benefits related to changes in the use of healthcare resources following a social prescribing intervention in four primary care practices in Wales. Methods: Quantitative data from routine healthcare usage was collected from the 78 participants pre and post intervention. The participants were grouped into frequent attenders (FA) (n=21) and frequent (n=57) non-attenders (FNA), and a cost analysis was conducted to estimate cost variances based on healthcare unit usage over the length of the pilot intervention. These were then extrapolated forward to identify potential healthcare savings. Results: The SP as an intervention generated the largest cost saving for FAs. The cost variance when FAs participated in the intervention shows there is a direct cost saving of £6,113 or £78.37 per participant over the five months of the intervention. Conclusions: Results suggest there is cost saving associated with SP interventions. The cost saving was largest for FAs, where the intervention reduced healthcare unit usage as well as actual and inferred impact on associated healthcare costs. This suggests that in practice to generate the maximum cost benefit SP interventions should be targeted at FAs.